Characterization of closed-die forged AZ31B under pure axial and pure shear loading. (October 2020) - Toscano, D.; Behravesh, S.B.; Shaha, S.K.; Jahed, H.; Williams, B.
Graphical abstract: Highlights: Forging of AZ31B extrusion results in significant changes in microstructure and texture. Texture evolution at any location depends on the corresponding plastic strain induced by closed-die forging. Forging process results in cyclic hardening and improved fatigue strength in AZ31B. Cyclic hysteresis response is asymmetric under axial but symmetric under shear loading. Multiple fatigue crack initiation cites observed under both axial and shear cyclic loads. Abstract: Extruded AZ31B was closed-die forged at a relatively low temperature of 250 °C. Quasi-static axial and shear tests in addition to cyclic pure axial and cyclic pure shear tests were performed to characterize the uniaxial response of the forged parts. To examine the effect of forging on the mechanical behavior of the material, quasi-static and fatigue response of the starting extruded AZ31B was also studied under axial loading. The forging process refined the grain structure and modified the crystallographic texture of the extruded AZ31B. The intensity of texture and the orientation of c-axis in the forged part were found to be controlled by the extent and the direction of plastic deformation, respectively. The modified microstructure resulted in insignificant effect on yield strength, slight decrease in ultimate strength, and enhanced failure strain of the forged AZ31B under axial loading. However, the forged AZ31B exhibited superior yield strength, similar ultimate strength, and lower failure strain under shear loading. The cyclic axial strength of the forging was similar to the starting extruded material under high strain amplitudes, but slightly superior under lower strain amplitudes, due to the development of a smaller tensile mean stress. The half-life hysteresis response for the forged material was asymmetric under large axial strain amplitudes, but it was symmetric under cyclic shear loading. This difference is originated from activation of twinning/ detwinning deformation under cyclic axial loading, while dislocation slip is the dominant deformation mechanism during cyclic shear loading. Fatigue fracture surface of forged AZ31B depicts that fatigue cracks were initiated from multiple locations under both cyclic axial and shear loadings.